NAPPE STRUCTURE OF THE NORTH SPORADES (GREECE): ON THE GEOLOGICAL EVOLUTION OF ALONNISOS ISLAND - Jacobshagen, V.; Matarangas, D. (Bulletin of the Geological Society of Greece, 2004)
On Alonnisos island detailed field studies were carried out concerning rock sequences and their boundaries, geochemical analyses of mafic volcanic rocks, and geological mapping of key areas in the southwestern and central parts of the island to the scale 1:10 000. In connection with already published data, our results led to a revision of the tectonic structure of the island and of its geological evolution. The deeper parts of Alonnisos are built up by Mesozoic rocks of the Pelagonian zone, locally with outliers of the Eohellenic nappe on top. Both units are covered by the well-known Mesoautochthonous sequence of Upper Cretaceous/Lower Tertiary age. These units are tectonically overlain by relics of the Palouki nappe, which consists of the probably Lower Cretaceous Palouki formation (once called "Palouki series"), followed by Upper Cretaceous marbles and by a metaflysch. This nappe was probably overthrust during the Eocebe (Mesohellenic) orogeny. Relics of the Palouki nappe can be followed from Alonnisos to Skopelos in the SW, over some small islands. As the rock association in its older parts point to a pelagic marine origin, we assume that the Palouki nappe had its origin in a relic of the Vardar ocean. Relations to other nappe ouliers, which hold a comparable position in the Sporades/Pelion region, are discussed.